Ownership Structure, Rent Seeking And Performance : Evidence From The Malaysian Manufacturing Sector (1994-2000) [HD1131. C559 2007 f rb]. - Chu, Ei Yet (2007)
Tesis ini mengkaji hubungkait antara struktur ekuiti dan nilai firma. Terdapat tiga objektif dalam kajian ini.